2013
DOI: 10.1007/978-3-642-45046-4_3
|View full text |Cite
|
Sign up to set email alerts
|

The Computational Complexity of Random Serial Dictatorship

Abstract: In social choice settings with linear preferences, random dictatorship is known to be the only social decision scheme satisfying strategyproofness and ex post efficiency. When also allowing indifferences, random serial dictatorship (RSD) is a well-known generalization of random dictatorship that retains both properties. RSD has been particularly successful in the special domain of random assignment where indifferences are unavoidable. While executing RSD is obviously feasible, we show that computing the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 8 publications
0
39
0
Order By: Relevance
“…The computational properties of RSD mentioned in Sect. 5 also hold within the domain of assignment [7,10,118].…”
Section: Random Assignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The computational properties of RSD mentioned in Sect. 5 also hold within the domain of assignment [7,10,118].…”
Section: Random Assignmentmentioning
confidence: 99%
“…6). While implementing RSD by uniformly selecting a sequence of agents and then running serial dictatorship is straightforward, it was shown that computing the resulting RSD probabilities is #P-complete [10], but fixed parameter tractable for parameters such as the number of voters or the number of alternatives [7].…”
Section: Probabilistic Social Choicementioning
confidence: 99%
“…A single run is clearly not sufficient, as we need to compare probability distributions. Note that computing probabilities of alternatives in RSD explicitly is a computationally very challenging (#P-complete) problem (Aziz et al 2013). Therefore, we ran BRSD 1000 to 1,000,000 times with the same preferences but random permutations of the order of students and derived estimates for the different metrics.…”
Section: Field Experimentsmentioning
confidence: 99%
“…The one-sided matching problem was introduced in [25] and has been studied extensively ever since. Over the years, several different mechanisms have been proposed with various desirable properties related to truthfulness, fairness and economic efficiency with Probabilistic Serial [2, 10,11,26] and Random Priority [3,8,15,37] being the two prominent examples. In the indivisible goods setting, the Top Trading Cycles (TTC) method is well-studied and generalized to investigate various problems.…”
Section: Related Workmentioning
confidence: 99%